Visual and Artefactual Approaches in Engaging Teachers with Multilingualism: Creating DLCs in Pre-Service Teacher Education - Nayr Correia Ibrahim (Languages, 2022)
This paper reports on a study of teachers’ engagement with their own multilingualism in a pre-service teacher education context. As linguistic diversity in society and schools around the globe is increasing, teachers are required to meet the challenges of teaching children who live with multiple languages. However, teachers are seldom required to reflect on and engage with their own multilingualism, which forms the basis of a subjective and experiential approach to educating teachers multilingually. Embedded in an arts-based visual methodology, this study used the concept of Dominant Language Constellations (DLCs) as both a theoretical underpinning and a creative qualitative tool for collecting data. It included fourteen DLC artefacts created by future teachers of English in Grades 1–7 and Grades 5–10 in northern Norway, supported by oral and written narratives. Plurisemiotic analysis of teachers’ DLC artefacts indicates that teachers ‘saw’ or perceived themselves as plurilingual individuals for the first time. Furthermore, they reflected on the classroom implications of including multilingual practices in a context of increasing linguistic diversity in Norway, through capitalizing on their own and potentially their learners’ multilingual identities.